Prisega ribjega tatu iz l. 1675 - Korošec, Tomo (Slavistična revija, 1996)
This is a still unpublished photocopy of a manuscript from the National and University Library in Ljubljana. A German record of a fish theft and the Slovene text of a fish thief's oath are from the official record book of the feudal dominion Polhov Gradec near Ljubljana. The article points out some characteristics of the administrative-legal texts from that period and the similiarities to the well-known Slovene oath formulas from the city of Ljubljana of approximately the same period.
Keywords: 17.st.; prisege; ribištvo; rokopisi; Slovene; slovenščina; zgodovinski pregledi